Effects of local aerosol and transported dust pollution on the surface energy balance over farmland in eastern China during spring - Zhou, Chuanru; Duan, Zexia; Ling, Xinfeng; Yang, Yuanjian (Frontiers in Environmental Science, 2023)
Compared with urban boundary layer, air pollution–surface energy budget interactions in the farmland areas are relatively sparse. To investigate the roles of the local aerosol and transport dust pollutions on surface energy balance over the cropland, a field experiment was conducted during 2016 spring in eastern China. The occurrences of typical heavy pollution episodes during the measurement period are often accompanied by easterly wind, lower wind speed, and higher relative humidity. Relative to clean days, both downward and upward shortwave radiation decreased by 46%, while downward and upward longwave radiation enhanced by 4% and 1% on polluted days. The combined effects of four radiation components resulted in a 26% reduction in net radiation on polluted days, and thus the surface energy budget changed. Polluted days had 15% (58 %) less sensible (latent) heat flux than clean days. This resulted in a higher daytime Bowen ratio on polluted days (0.83 than that on clean days (0.44). In a case analysis of dust pollution, high wind speed and the continuous high pressure induced the outbreak of the dust pollution episodes. Compared to the local pollution events, the latent (sensible) heat flux was reduced more (less) than that in the transport dust pollution. Generally, this work has important implications for other farmland regions to design effective source emission mitigation practices.